Dimethylfumarate effectively inhibits lymphangiogenesis via p21 induction and G1 cell cycle arrest. Issue 3 (10th February 2016) - Valesky, Eva Maria; Hrgovic, Igor; Doll, Monika; Wang, Xiao‐Fan; Pinter, Andreas; Kleemann, Johannes; Kaufmann, Roland; Kippenberger, Stefan; Meissner, Markus
Abstract: Different pathologies, such as lymphoedema, cancer or psoriasis, are associated with abnormal lymphatic vessel formation. Therefore, influencing lymphangiogenesis is an interesting target. Recent evidence suggests that dimethylfumarate (DMF), an antipsoriatic agent, might have antitumorigenic and antilymphangiogenic properties. To prove this assumption, we performed proliferation and functional assays with primary human dermal lymphendothelial cells (DLEC). We could demonstrated that DMF suppresses DLEC proliferation and formation of capillary‐like structures. Underlying apoptotic mechanisms could be ruled out. Cell cycle analysis demonstrated a pronounced G1‐arrest. Further evaluations revealed increases in p21 expression. In addition, DMF suppressed Cyclin D1 and Cyclin A expression in a concentration‐dependent manner. p21 knockdown experiments demonstrated a p21‐dependent mechanism of regulation. Further analysis showed an increased p21 mRNA expression after DMF treatment. This transcriptional regulation was enforced by post‐transcriptional and post‐translational mechanisms. In addition, we could demonstrate that the combination of a proteasomal inhibitor and DMF superinduced the p21 expression. Hence, DMF is a new antilymphangiogenic compound and might be used in various illnesses associated with increased lymphangiogenesis.